Structural simulation study of oil, gas and water separation equipment - Chen Xiaoxuan; Lv Yuling (E3S Web of Conferences)
As the oilfield enters the medium-high water content period, the load of the existing treatment equipment in the oilfield increases, the degree of emulsification of the extracted fluid is high, and the three- phase separation technology of oil, gas and water needs to be further optimized; the limited processing space of the offshore oil and gas extraction platform puts forward higher requirements for the floor space of the separation equipment, so it is crucial to design a highly efficient and compact oil, gas and water separation equipment. In this paper, a combination of liquid distribution tube inlet member, field plate rectification member and single hole serpentine plate phase-parallel plate group aggregation structure is selected through literature research, and an oil, gas and water separation equipment is designed. Afterwards, the internal flow field is simulated by Fluent software to visualize the internal separation effect of the three-phase separator. From the simulation results, it can be seen that the oil-water separation effect of this separation equipment is better, and the velocity of the internal flow field is appropriate, which indicates that this oil-gas-water separation equipment is effective in improving the oil-water separation effect.